2021
DOI: 10.3389/fneur.2021.633492
|View full text |Cite
|
Sign up to set email alerts
|

Volume Rendering of Angiographic Optical Coherence Tomography Angiography in Fovea Plana and Normal Foveal Pit

Abstract: This paper aims to study adaptative vascular arrangements in idiopathic fovea plana with volume-rendered optical coherence tomography angiography (OCTA). A retrospective review of two cases of idiopathic fovea plana (mean age: 26.5 years) and two age-matched controls imaged with OCTA was conducted using spectral-domain OCTA (RTVue XR Avanti, Optovue, Inc., Fremont, CA) equipped with the AngioVue software. Both en face OCTA slabs and OCTA b scans were processed through Fiji software (http://fiji.sc; software ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Finally, in the literature, there are reports assessing the impact of the 3D representation of macula blood vessels [25][26][27][28][29][30][49][50][51][52]. These methods were based on surface and volumetric rendering [25, 28-30, 49, 50, 52] of the original 3D OCTA volume or they interpolated the 3D representation from 2D OCTA B-scans [26,27,51].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, in the literature, there are reports assessing the impact of the 3D representation of macula blood vessels [25][26][27][28][29][30][49][50][51][52]. These methods were based on surface and volumetric rendering [25, 28-30, 49, 50, 52] of the original 3D OCTA volume or they interpolated the 3D representation from 2D OCTA B-scans [26,27,51].…”
Section: Discussionmentioning
confidence: 99%
“…These methods were based on surface and volumetric rendering [25, 28-30, 49, 50, 52] of the original 3D OCTA volume or they interpolated the 3D representation from 2D OCTA B-scans [26,27,51]. They succeeded in generating a 3D depiction of the macula's volume [25][26][27][49][50][51], or they developed methods to generate a 3D shape model [28], map [29,52], and surfacing the macula vasculature [30]. Similar to the OCTA quantitative metrics discussion in the preceding paragraph, the aim was to assess the integrity or the disruption of the macula blood vessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While previous studies have explored structural and functional abnormalities in FH, limited research has focused on specific changes in retinal FD and FAZ parameters in OCTA imaging. Due to the relative rarity of FH and the novelty of OCTA technology, most studies reporting on changes in microvascular parameters in FH patients have been limited to case series, depicting qualitative rather than quantitative data [9][10][11][12][13][14][15][16][17]. The studies which report quantitative data have demonstrated that while FH is associated with a reduction in FD in whole en face scans, it shows increased FD values in the foveal sector in the inner retinal plexus [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to magnetic resonance imaging, OCT and OCTA have emerged as beneficial imaging tools in multiple sclerosis 15 . The retinal vessel volume-rendering showed the altered microcirculation in the macula, for example in fovea plana, which is important because these eyes cannot fit into the scheme of normative data banks offered by the commercial manufacturers 16 .…”
Section: Introductionmentioning
confidence: 99%